2019
DOI: 10.7150/ijms.30832
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Printed Porous Titanium Alloy Rod with Diamond Crystal Lattice for Treatment of the Early-Stage Femoral Head Osteonecrosis in Sheep

Abstract: Instruments made of porous titanium alloy and fabricated with a 3D printed technique are increasingly used in experimental and clinical research. To date, however, few studies have assessed their use in early-stage osteonecrosis of the femoral head (ONFH). In this study, porous titanium alloy rods (Ti-Rod) with diamond crystal lattice, fabricated using an electron beam melting (EBM) technique, were implanted into sheep models (n=9) of early-stage ONFH for 6 months. Bone ingrowth and integration were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…At 6 months, another 4 animals were sacrificed, and the femurs were harvested and stored at −80 centigrade. The testing process was similar with previous reports [ 12 , 13 ]. Briefly, using a self-designed clamping apparatus, the proximal femurs were fixed on a universal mechanical testing machine (AGS 10 KNG, SHIMADZU, Japan).…”
Section: Methodssupporting
confidence: 71%
“…At 6 months, another 4 animals were sacrificed, and the femurs were harvested and stored at −80 centigrade. The testing process was similar with previous reports [ 12 , 13 ]. Briefly, using a self-designed clamping apparatus, the proximal femurs were fixed on a universal mechanical testing machine (AGS 10 KNG, SHIMADZU, Japan).…”
Section: Methodssupporting
confidence: 71%
“…30 One limitation of this study is that the animal model was a sheep model; although this is a better model than small animal models, such as rabbit and rat models, the mechanical environment of the femur in quadrupeds is not as similar to that in humans as that in bipeds. 31…”
Section: Discussionmentioning
confidence: 99%
“…With the advantages of additive manufacturing, 3D-printed customized prosthesis could add porous bone trabecular-like structures to promote bone ingrowth and promote bone and prosthesis interface integration, which play an important role in bone defect reconstruction and repair. Previous studies showed that the porous structures with 300 to 800 µm pore-size and 70% porosity can enhance bone ingrowth (19)(20)(21)(22)(23). So porous structures with porosity of 70% and poro-size of 600 µm were applied in this study, and osseointegration was well observed in patients.…”
Section: Discussionmentioning
confidence: 93%